HOW DO GREEK-CYPRIOT PRIMARY SCHOOL TEACHERS PERCEIVE PROFESSIONAL DEVELOPMENT? - Nicolaou, Lefki (2010)
The Cypriot Ministry of Education acknowledges the importance of professional development and offers a number of activities in order to continue qualifying teachers. However, the activities offered are limited and are mainly traditional. There is a need to understand the degree to which reforming professional development activities can be successfully introduced into the Cypriot Educational context. Studying teachers‟ perceptions about professional development helps to understand which their needs are, how these needs can be met, and which the potentials to introduce more effective activities are.